2019
DOI: 10.9734/arjom/2019/v14i430135
|View full text |Cite
|
Sign up to set email alerts
|

Keller-box Study on Casson Nano Fluid Flow over a Slanted Permeable Surface with Chemical Reaction

Abstract: In this problem, an examination of Casson Nanofluid boundary layer flow over linear slanted extending sheet by fusing the chemical reaction and heat generation impacts are under thought. Nanofluid demonstrate in this examination is developed on Buongiorno model for the thermal efficiencies of the liquid flow in the presence of Brownian movements and thermophoresis impacts. The nonlinear issue for Casson Nanofluid flow over slanted channel is displayed to ponder the heat and mass exchange wonder by considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The flow of free convection fluid through a slanted sheet was elucidated by Sheri and Modugula [13]. Recently, different researchers studied the heat and mass exchange phenomenon with different impacts, see [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The flow of free convection fluid through a slanted sheet was elucidated by Sheri and Modugula [13]. Recently, different researchers studied the heat and mass exchange phenomenon with different impacts, see [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Some processes are power plants for power generation, spacecrafts engines, space exploration, hypersonic light and solar power devices. In view of such important reasons, many researchers [37][38][39][40] have been reported various studies in this direction.…”
Section: Introductionmentioning
confidence: 99%
“…Hatami et al [22] discussed three-dimensional steady nanofluids over an inclined disk. Recently, Rafique et al [23] investigated the Casson nanofluid flow towards an inclined surface and found that the inclination effect retards the velocity profile.…”
Section: Introductionmentioning
confidence: 99%